Optimalisasi Pembelajaran Biologi melalui Pengembangan Lembar Kerja Peserta Didik Berbantuan Augmented Reality - Suryaningsih, Yeni; Rasyid, Abdur; Nurmalawaty, Nabila; Kartini (Papanda Journal of Mathematics and Science Research, 2024)
This study aims to improve the effectiveness of learning through the development of Student Worksheets (LKPD) by utilizing Augmented Reality (AR) technology. By combining the concept of traditional LKPD with AR, this study creates an innovation in the delivery of learning materials. Learning methods integrated with AR can provide a more interactive and immersive learning experience for students. Augmented Reality LKPD assisted by Augmented Reality is designed for various subjects, presenting interesting and dynamic visualizations. The main benefit of this study is to increase student engagement and understanding in learning. By utilizing AR technology, this study also has the potential to change the traditional paradigm of learning into a more modern and relevant experience with current technological developments. The results of the validity of LKPD experts assisted by Augmented Reality by material experts are 79%, learning media design experts are 80%, language experts are 85%, and lecturers/practitioners' assessments are 88% with a very valid category. For the results of large-scale trials of media, the results are 78.4% with interesting criteria. Keywords: Student Worksheets, Augmented Reality